THE ROLE OF EMPLOYEE WELL-BEING IN FOSTERING ORGANIZATIONAL CITIZENSHIP BEHAVIOR: A LITERATURE REVIEW - Eko Santoso; Desi Rahmawati (Berajah Journal, 2026)
Employee welfare is one of the important factors in human resource management that plays a role in shaping positive work attitudes and behaviors. One of the behaviors that has received attention in the organizational behavior literature is Organizational Citizenship Behavior (OCB), which is the voluntary behavior of employees that is carried out outside of formal duties and contributes to the effectiveness of the organization. This study aims to analyze the role of employee welfare in encouraging Organizational Citizenship Behavior and identify the factors that affect the relationship between the two. This research uses a library research method with a qualitative descriptive approach through the study of various relevant literature in the field of human resource management and organizational behavior. The results of the study show that employee welfare generally consists of psychological, emotional, social, and work environment dimensions that together affect employee work behavior. Various studies show that there is a positive relationship between employee well-being and Organizational Citizenship Behavior which is reflected through increased behavior of helping colleagues, concern for the organization, work responsibilities, and active participation in organizational activities. The study also found that job satisfaction, employee engagement, organizational commitment, organizational support, leadership support, and work-life balance are factors that can strengthen the relationship between employee well-being and Organizational Citizenship Behavior. Conversely, burnout and work stress have the potential to weaken those relationships. These findings confirm that employee well-being is a strategic resource that not only improves the quality of employees' working lives, but also encourages voluntary behaviors that support organizational effectiveness and sustainability.